Marketing Strategy Analysis on the Competitive Advantage of Culinary MSMEs in Makassar City - Rachmawaty, Rachmawaty; Riesso, Andi Sawe; Angka, Andi Werawe; Nurdiana, Nurdiana; Hasanah, Dillah Faradillah (Economic Education and Entrepreneurship Journal, 2023)
This article analyzes the marketing strategies culinary Small and Medium Enterprises (SMEs) in Makassar City to maintain a competitive advantage. This study aims to understand effective marketing strategies in increasing the competitiveness of culinary SMEs in the local market. The research method used is qualitative with data collection techniques with data-based mass media, ebooks, journals, and online news portals. The analysis results show that effective marketing strategies include using social media, superior product quality, product differentiation, local promotion, and partnerships with local suppliers. In the face of intense competition, culinary SMEs need to consider these factors to remain the main choice of consumers. This article provides insights and recommendations for other culinary SMEs who want to increase their competitive advantage in Makassar City.Keywords: Markets, Strategy, Small and Medium EnterprisesDOI: http://dx.doi.org/10.23960/E3J/v6i1.83-88